2022
DOI: 10.1155/2022/6600278
|View full text |Cite|
|
Sign up to set email alerts
|

Applications of Bladder Cancer Data Using a Modified Log-Logistic Model

Abstract: In information science, modern and advanced computational methods and tools are often used to build predictive models for time-to-event data analysis. Such predictive models based on previously collected data from patients can support decision-making and prediction of clinical data. Therefore, a new simple and flexible modified log-logistic model is presented in this paper. Then, some basic statistical and reliability properties are discussed. Also, a graphical method for determining the data from the log-logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…This dataset was collected from bladder cancer patients and reported by Lee and Wang (2003). It has been studied in detail by Ieren et al (2019), Ijaz et al (2020), andKayid (2022). The real-life data contains a set of remission times (in months) from 128 bladder cancer patients which is represented in Table 6.…”
Section: The Remission Time Of the Bladder Cancer Patients Datasetmentioning
confidence: 99%
“…This dataset was collected from bladder cancer patients and reported by Lee and Wang (2003). It has been studied in detail by Ieren et al (2019), Ijaz et al (2020), andKayid (2022). The real-life data contains a set of remission times (in months) from 128 bladder cancer patients which is represented in Table 6.…”
Section: The Remission Time Of the Bladder Cancer Patients Datasetmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%